2013
DOI: 10.3892/mco.2013.202
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy of promoting cisplatin chemotherapeutic efficiency by targeting endoplasmic reticulum stress

Abstract: Abstract. Cisplatin (cis-diamminedichloroplatinum II, CDDP) is one of the most effective chemotherapeutic agents and is widely used in the treatment of solid tumors. However, its side effects and acquired resistance gained during the course of treatment may limit its usage. It is generally considered to be a cytotoxic drug that kills cancer cells by damaging their DNA and inhibiting DNA synthesis to induce apoptosis via the mitochondrial death pathway or through plasma membrane disruption, triggering the Fas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 37 publications
3
41
0
Order By: Relevance
“…This suggests that regulation of p53 activity may be an important target for alleviating cisplatin nephrotoxicity. cisplatin nephrotoxicity is also associated with endoplasmic reticulum (ER) stress (16). Pre-activation of ER stress alleviates cisplatin-induced nephrotoxicity in various renal cell lines (17).…”
Section: Phosphorylation Of Eif2α Suppresses Cisplatin-induced P53 Acmentioning
confidence: 99%
“…This suggests that regulation of p53 activity may be an important target for alleviating cisplatin nephrotoxicity. cisplatin nephrotoxicity is also associated with endoplasmic reticulum (ER) stress (16). Pre-activation of ER stress alleviates cisplatin-induced nephrotoxicity in various renal cell lines (17).…”
Section: Phosphorylation Of Eif2α Suppresses Cisplatin-induced P53 Acmentioning
confidence: 99%
“…Cisplatin resistance may be associated with the altered regulation of multiple signaling pathways, including downregulation of apoptotic signals, and activation of pro-survival signals (Ali et al 2012;Gal-luzzi et al 2012;Davis et al 2014). Recent studies have shown that endoplasmic reticulum (ER) stress-associated apoptosis can be induced by cisplatin, and that ER stress tolerance may be involved in cisplatin resistance (Xu et al 2012(Xu et al , 2014(Xu et al , 2015a.…”
Section: Introductionmentioning
confidence: 99%
“…The ER is the most critical protein-folding compartment and an intracellular Ca 2+ storage organelle in cells (25). Thus, accumulating reactive nitrogen species could modify proteins and disrupt Ca 2+ homeostasis, which may trigger the induction of cisplatin-induced ER stress (26,27). Upon cisplatin treatment, intracellular NO levels increased nearly by 10-fold in the Mahlavu cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that cisplatin-induced ER stress response simultaneously provoked two prominent pathways that may induce cells apoptosis. The key effectors of ER stress-signaling pathways may modulate cisplatin-induced cell death (27) through GRP78 (24) or β-catenin (28). Therefore, identifying those molecules that can be used to predict cisplatin treatment response would enable therapy to be tailored on an individual HCC patient basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation